Transnationalism and the History of Historiography: A Transatlantic Perspective - Stelzel, Philipp (History compass, 2015)
This essay discusses recent research in the history of historiography. Much of this scholarship has been written from a comparative perspective. Even more recently, historiographical studies have turned to transnational approaches. The essay surveys the field and discusses the chances as well as the limitations of this "transnational turn." While transnational approaches can contribute new insights into historiographical developments, one should see them as complementary rather than as a replacement for microhistorical, national, or comparative foci.